Chemically Driven Tunable Light Emission of Charged and Neutral Excitons in Monolayer WS2 - Peimyoo, Namphung; Yang, Weihuang; Shang, Jingzhi; Shen, Xiaonan; Wang, Yanlong; Yu, Ting (ACS nano, 2014)
Monolayer (1L) semiconducting transition metal dichacogenides (TMDs) possess remarkable physical and optical properties, promising for a wide range of applications from nanoelectronics to optoelectronics such as light-emitting and sensing devices. Here we report how the molecular adsorption can modulate the light emission and electrical properties of 1L WS2. The dependences of trion and exciton emission on chemical doping are investigated in 1L WS2 by microphotoluminescence (μPL) measurements, where different responses are observed and simulated theoretically. The total PL is strongly enhanced when electron-withdrawing molecules adsorb on 1L WS2, which is attributed to the increase of the exciton formation due to charge transfer. The electrical transport measurements of a 1L WS2 field effect transistor elucidate the effect of the adsorbates on the conductivity, which give evidence for charge transfer between molecules and 1L WS2. These findings open up many opportunities to manipulate the electrical and optical properties of two-dimensional TMDs, which are particularly important for developing optoelectronic devices for chemical and biochemical sensing applications.